In vitro Assessment of Antiviral Effect of Natural Compounds on Porcine Epidemic Diarrhea Coronavirus - Gómez-García, Manuel; Puente, Héctor; Argüello, Héctor; Mencía-Ares, Óscar; Rubio, Pedro; Carvajal, Ana (Frontiers in Veterinary Science, 2021)
Organic acid and essential oils (EOs), well-known antimicrobials, could also possess antiviral activity, a characteristic which has not been completely addressed up to now. In this study, the effect of two organic acids (formic acid and sodium salt of coconut fatty acid distillates) and two EOs (thymol and cinnamaldehye) was evaluated against porcine epidemic diarrhoea virus (PEDV). The concentration used for each compound was established by cytotoxicity assays in Vero cells. The antiviral activity was then evaluated at three multiplicities of infection (MOIs) through visual cytopathic effect (CPE) evaluation and an alamarBlue assay as well as real-time reverse-transcription PCR (RT-qPCR) and viral titration of cell supernatants. Formic acid at at a dose of 1,200 ppm was the only compound which showed antiviral activity, with a weak reduction of CPE caused by PEDV. Through the alamarBlue fluorescence assay, we showed a significant anti-CPE effect of formic acid which could not be observed by using an inverted optical microscope. RT-qPCR and infectivity analysis also showed that formic acid significantly reduced viral RNA and viral titers in a PEDV MOI-dependent manner. Our results suggest that the antiviral activity of formic acid could be associated to its inhibitory effect on viral replication. Further studies are required to explore the anti-PEDV activity of formic acid under field conditions alone or together with other antiviral agents.